EKSISTENSI FILSAFAT KOMUNIKASI DI ERA DIGITAL - Kusumasanthi, Dewi; Wiguna, Ida Bagus Alit Arta; Puspawati, Srirahayu (IAHN Gde Pudja Mataram, 2023)
This research aims to find the existence of communication philosophy in the progress of the times such as the rapid development of technology in the digital era. In addition, it has a more in-depth purpose related to the application of the philosophy of communication in everyday life. This research uses a qualitative research method with a library research approach or called content analysis. This research is conducted with critical analysis and interpretation of various search results from primary and secondary sources. So as to produce a new understanding and concept in the philosophy of communication according to the times and the implementation of the necessary communication ethics.